Persepsi Mahasiswa terhadap Indikator Prinsip Pelayanan Publik dan Berbagai Kelemahan dalam Pelayanan Publik di Tujuh Perguruan Tinggi di Indonesia - Setiawati, Asih (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2018)
The objectif or research are to determine student perceptions about indicators of quality of service of universities from lecturer and administrative personnel, forms of services and things that are still weak in quality services in universities. The data were supplemented using a questionnaire consisting of closed and open questions. The number of samples analyzed were 370 respondents, using purposive sampling method at seven universities in Indonesia. Quantitative data analysis used is the validity, reliability test, and descriptive statistics, while qualitative data are analyzed using the contents. The results show that in general the students agree with the high quality indicators of higher education developed. Agreement on the non-discrimination and the lowest aspects of the aspect of easy and cheap. Students who need high service should be without discrimination but still allow for better service seen from the ease and generosity in the service. In general, students demand all universities that have run a quality service. Even so there are various problems that still need to be fixed. There are four problems with aspect, problem, problem solution, problem solution, problem solution, and problem, and problem, accountability, problem and ethics. Steps need to be taken to improve student perceptions of the importance of college public indicators and improvements to issues united by students on the services of higher education.